2021
DOI: 10.1186/s12906-021-03327-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the bone sparing effects of postbiotics in the post-menopausal rat model

Abstract: Background Post-menopausal osteoporosis is a concern of health organizations, and current treatments do not seem enough. Postbiotics as bioactive compounds produced by probiotics may be an attractive alternative for bone health. In this study, we prepared, formulated, and compared the effects of cell lysate and supernatant of five native probiotic strains (Lactobacillus acidophilus, Lactobacillus reuteri, Lactobacillus casei, Bifidobacterium longum, and Bacillus coagulans) in ovariectomized (OV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 49 publications
(56 reference statements)
2
20
0
Order By: Relevance
“…Postbiotics is an umbrella term that includes metabolites, SCFAs, microbial cell fractions, functional proteins, extracellular polymeric substances (EPSs), cell lysates, teichoic acid, peptidoglycan-derived muropeptides, and pili-type structures, which may be used to promote health by modulating the gut microbiota [ 153 ]. In this context, only a few very recent studies [ 154 , 155 , 156 ] have shown how the administration of postbiotics ameliorates osteopenia and/or osteoporosis. A study of the effects of cell lysates and supernatants of five native probiotic strains ( L. acidophilus , L. reuteri , L. casei , B. longum , and B. coagulans ) in ovariectomized rats showed that the Bacillus -coagulans-derived-postbiotics had the best impact on bone homeostasis, ameliorating several parameters, such as reduced bone area, bone mineral content, and BMD caused by ovariectomy [ 153 ].…”
Section: Interventional Microbiota Modulation To Reduce Bone Lossmentioning
confidence: 99%
“…Postbiotics is an umbrella term that includes metabolites, SCFAs, microbial cell fractions, functional proteins, extracellular polymeric substances (EPSs), cell lysates, teichoic acid, peptidoglycan-derived muropeptides, and pili-type structures, which may be used to promote health by modulating the gut microbiota [ 153 ]. In this context, only a few very recent studies [ 154 , 155 , 156 ] have shown how the administration of postbiotics ameliorates osteopenia and/or osteoporosis. A study of the effects of cell lysates and supernatants of five native probiotic strains ( L. acidophilus , L. reuteri , L. casei , B. longum , and B. coagulans ) in ovariectomized rats showed that the Bacillus -coagulans-derived-postbiotics had the best impact on bone homeostasis, ameliorating several parameters, such as reduced bone area, bone mineral content, and BMD caused by ovariectomy [ 153 ].…”
Section: Interventional Microbiota Modulation To Reduce Bone Lossmentioning
confidence: 99%
“…Recently, lot of research attention has been paid to understand the emerging role of gut microbiota in regulating the dynamic bone remodelling process. Augmentation of gut microbiota through ingestion of prebiotics/probiotics has been identified as a novel and effective strategy to regulate the deranged bone remodelling process induced due to a number of pathologic conditions that accelerate bone loss, weakens the bone and lead to systemic skeletal diseases like osteoporosis 70 . One of the early reports implicating the effects of gut microbiota on bone was by Sjogren et al 71 .…”
Section: The Protective Effects Of Probiotics On Bonementioning
confidence: 99%
“…Osteoporosis, a skeletal disease described by impaired bone strength that causes an increased risk of fractures, is a worldwide disease that mainly occurs in postmenopausal women and older adults [ 1 , 2 ]. The condition is a bothering factor for about 200 million people, with low bone mass, worsening of the fine structure of bone tissue, and elevated chance of fractures [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many experiments have been recently done to specify the potential profits of probiotic preparations in pathologic bone disorders such as osteoporosis. In this regard, several probiotic strains have been introduced in a single administration or as food supplementation to ameliorate bone loss [ 2 ]. Oral intake of a single probiotic strain Limosilactobacillus reuteri ( L. reuteri ) for 28 days by male rat caused substantial health benefits for trabecular bone density, number, thickness, and bone mineral content and density both in the femur and vertebral [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation